If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3x = -5x + -2 Reorder the terms: 6 + -3x = -2 + -5x Solving 6 + -3x = -2 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 6 + -3x + 5x = -2 + -5x + 5x Combine like terms: -3x + 5x = 2x 6 + 2x = -2 + -5x + 5x Combine like terms: -5x + 5x = 0 6 + 2x = -2 + 0 6 + 2x = -2 Add '-6' to each side of the equation. 6 + -6 + 2x = -2 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = -2 + -6 2x = -2 + -6 Combine like terms: -2 + -6 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 2x-3x=3-x | | a-16/18=8/9 | | 1/6(5x-9)=7 | | 7-x=6+14 | | 8-4=x+1 | | 6x+4x=10 | | y=x^2*ln(x+2) | | 15x+3y=39 | | 1200=0.18*x | | 1200=0.18x | | -3/4+3/2-2 | | -3x-3x=48-6 | | t^2+7t-18=T+1 | | -19.95-1.10x=-2.35 | | f(x)=3x^3-4x^2 | | 2x^2-5x-38=0 | | y=-2(x-3)+4 | | (2x-5)=1 | | 5/6x=30 | | 7x-1=8x-4 | | 3(2x-3)+5=17 | | 3x+8=8x-22 | | -13-x=-5 | | -5.00-4.00x=53.00 | | 3(x-1)-2(x+4)=10 | | -135-20(x-4)=24x | | 6y^4-12y^3+4y^2= | | 4-x=5x+10 | | -65+7(x+7)=-3-4(x-5) | | -6(x+7)=20 | | 17=6(x-2) | | --4-3*5= |